Strategi Misi Paulus dalam Perintisan Gereja Menurut Kisah Para Rasul dan Implikasinya Bagi Hamba Tuhan - Kristina Anita Sari Laia; Mozes Lawalata (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
Today’s church planting is no longer as expected as the early church. Where they do pioneering on the basis of truth. Church transfers occur due to the existence of a new church that facilitates the church which triggers people to move from the local church to another church. For this reason, this article aims to answer problems that ofthen occur in the church today. This research was written using qualitative methods, as well as documents to support this writing. Based on the results of the study above, the Apostle Paul’s strategy in carrying out church planting was first, evangelizing to cities, secondly visiting synagogues, thirdly preaching around and fourthly in planting the apostle Paul’s church using his colleagues in church growth. The final conclusion of writing is that the Servant of God. Back to the early church that is based on the truth of God’s Word.